Effect of Tribology on Multifunctional Coating Surface/Interface - Siti Maznah, Kabeb (CRC Press, 2025)
Increasing demand for tribological applications has led to the use of multifunctional coatings to fulfill specific requirements. This chapter reviews the fundamentals of tribology, followed by current advancements in multifunctional coatings which are using acceptable approaches to provide protection in tribological applications. The chapter also highlights the mechanism related to the factors that dictate the wear and friction behavior of the coatings. Critical insights into the role of multifunctional coatings on tribology and important aspects of engineering surfaces are also discussed in this chapter.